Hemangioma with Basophilic Bodies- A Diagnostic Challenge - Rijhsinghani, Archana N; Deshpande, Jaya R (Annals of Pathology and Laboratory Medicine, 2022)
The main location of hemangiomas is the head and neck, followed by the trunk and limbs. We present an unusual case of hemangioma with basophilic bodies, which created a diagnostic dilemma. This case had a scalp swelling which was excised and sent for histological examination. It turned out to be a hemangioma on microscopy, however, showed some basophilic structures on the surface of the lesion which were difficult to decode. This case gives us a lesson that only turning pages of a book doesn’t suffice, knowing a detailed clinical history followed by analysis of the same helps in final conclusive diagnosis.